Inaugural Lecture : Rejuvenation of an old crop :|broles of sago in the food and energy industries - Kopli, Bujang (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Sago palm, while being secondary to oil-palm in its perception and application, is seen as the next crop that deserves prompt and proper attention. Much praise has been given to this palm, which can grows almost unaided and naturally in swamps and areas whereas inhabitable by other crops, without serious requirements for fertilizers and pesticides. Also, the palm is able to regenerate without the need for replanting through its numerous suckers, hence providing a continuous supply of new and young palms upon harvesting of the mother palm. Apart from the long wait upon first planting, it is the world's highest producer of starch at 25tons/ha. Concerted efforts are underway to shorten the 10 year maturity period, and also to increase the starch yield. The starch has been shown to be easily digestible by most enzymes for hydrolysis to glucose, the first step whereby numerous other products can be generated. This includes sugars (mainly glucose) that can be commercialized for public consumption or as the substrate to produce lactic acid - which is an expensive base for the biopolymer, preservatives and cosmetic industries. Other than that, fermentation of the sago sugar into bioethanol is another option. While it is highly uneconomical to produce bioethanol from starch due to the small differences in the price of the raw material and the product, producing sugar from sago hampas (separated from sago effluent) for the same purpose is totally feasible. Systematic enzymatic treatments of the separated fibres can generate fermentable sugars to a yield of about 40-50%. Using hampas will cut the cost by almost 90% and concomitantly reduces environmental pollution. While the starch extraction process has been shortened to less than an hour in most modern factories in Sarawak to produce pure and dried starch, the process itself still generates voluminous amount of effluent containing some residual starch and fibres. Rather than perceived as a problem, the effluent is recognized as a raw material to produce food through the culture of micro-algae for production of protein or biodiesel.